1994
DOI: 10.1007/bf02412362
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic fibroma of bone: a report of 18 cases

Abstract: Desmoplastic fibroma is a rare benign primary bone tumor, histologically identical to the extra-abdominal desmoid tumor of soft tissues. The incidence in major series of bone tumors is 0.1%-0.3%. In the present study 18 cases from the files of the Netherlands Committee on Bone Tumors are reported, with an emphasis on the radiographic features. Eight female and ten male subjects were affected, with a fairly even age distribution from the second to the seventh decade of life. The most frequent sites of involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 10 publications
1
29
0
6
Order By: Relevance
“…16,20 Classically, DFs have been described as slow growing and relatively benign. 3,24,28 However, this description is not consistent with the DFs we encountered in our two patients; those tumors caused bony destruction and mediastinal compression leading to hypotension over a relatively short period of time. New genetic studies have shown that DFs have the potential to develop malignant transformation characteristics.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…16,20 Classically, DFs have been described as slow growing and relatively benign. 3,24,28 However, this description is not consistent with the DFs we encountered in our two patients; those tumors caused bony destruction and mediastinal compression leading to hypotension over a relatively short period of time. New genetic studies have shown that DFs have the potential to develop malignant transformation characteristics.…”
mentioning
confidence: 55%
“…22 Although DF accounts for only 0.1%-0.3% of all bone tumors and is typically characterized as a slow-growing benign lesion, 28 it can be locally aggressive and cause destruction of bone and soft tissue. 11 In addition, DF is notorious for local recurrence even after resection 10 and, on rare occasions, can grow quickly, causing significant morbidity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of choice, therefore, is wide tumor resection. Taconis et al in their analysis of 18 cases of desmoplastic tumor, found no recurrence occurring after 9-year follow-up in patients treated with wide resection [2].…”
Section: Diagnosis: Desmoplastic Fibroma Of the Bonementioning
confidence: 96%
“…Clinically, the commonest presentation is pain, palpable mass, and swelling; although it may be discovered as incidental finding on imaging. The lesion may also become evident after a pathological fracture [2]. The majority of cases are reported in patients younger than 30 years of age.…”
Section: Diagnosis: Desmoplastic Fibroma Of the Bonementioning
confidence: 99%